A cell-autonomous requirement for CXCR4 in long-term lymphoid and myeloid reconstitution - Kawabata, Kenji (The National Academy of Sciences, 1999)
Mice lacking the chemokine stromal cell-derived factor/pre-B cell growth stimulating factor or its primary physiological receptor CXCR4 revealed defects in B lymphopoiesis and bone marrow myelopoiesis during embryogenesis. We show here that adoptive transfer experiments reveal a deficiency in long-term lymphoid and myeloid repopulation in adult bone marrow by CXCR4−/− fetal liver cells, although stromal cell-derived factor/pre-B cell growth stimulating factor−/− fetal liver cells yield normal multilineage reconstitution. These findings indicate that CXCR4 is required cell autonomously for lymphoid and myeloid repopulation in bone marrow. In addition, CXCR4−/− fetal liver cells generated much more severely reduced numbers of B cells relative to other lineages in bone marrow. Furthermore, the repopulation of c-kit(+) Sca-1(+) lin(low/−) cells by CXCR4−/− fetal liver cells was less affected compared with c-kit(+) Sca-1(−) lin(low/− )cells. By previous studies, it has been shown that c-kit(+) Sca-1(+) lin(low/− )cells are highly purified primitive hematopoietic progenitors and that c-kit(+) Sca-1(−) lin(low/− )cells are more committed hematopoietic progenitors in mice. Thus, CXCR4 may play an essential role in generation and/or expansion of early hematopoietic progenitors within bone marrow.